Deposition of Hybrid Photocatalytic Layers for Air Purification Using Commercial TiO2 Powders - Ewoud Cosaert; Cédric Wolfs; Stéphanie D. Lambert; Geraldine J. Heynderickx; Dirk Poelman (Molecules, 2021)
Photocatalytic nanomaterials, using only light as the source of excitation, have been developed for the breakdown of volatile organic compounds (VOCs) in air for a long time. It is a tough challenge to immobilize these powder photocatalysts and prevent their entrainment with the gas stream. Conventional methods for making stable films typically require expensive deposition equipment and only allow the deposition of very thin layers with limited photocatalytic performance. The present work presents an alternative approach, using the combination of commercially available photocatalytic nanopowders and a polymer or inorganic sol–gel-based matrix. Analysis of the photocatalytic degradation of ethanol was studied for these layers on metallic substrates, proving a difference in photocatalytic activity for different types of stable layers. The sol–gel-based <semantics>TiO2</semantics> layers showed an improved photocatalytic activity of the nanomaterials compared with the polymer <semantics>TiO2</semantics> layers. In addition, the used preparation methods require only a limited amount of photocatalyst, little equipment, and allow easy upscaling.